Synovial incorporation of polyacrylamide hydrogel after injection into normal and osteoarthritic animal joints. Issue 11 (November 2016) - Christensen, L.; Camitz, L.; Illigen, K.E.; Hansen, M.; Sarvaa, R.; Conaghan, P.G.
Summary: Objective: Polyacrylamide hydrogel (PAAG) is a non-toxic, non-degradable synthetic product, used for years in the augmentation of soft tissues. Preliminary results in animals and humans have suggested long-lasting beneficial effects on symptoms of osteoarthritis (OA). The aim of this histopathological study was to investigate whether intra-articular injection of PAAG is integrated into synovial tissue in normal and OA animal joints, and if this integration is sustained. Methods: (A) A prospective, controlled, longitudinal study of normal knee joints injected with PAAG was performed in 10 rabbits, following the animals up to 1 year, and (B) a post mortem examination was carried out up to 2 years post-injection on 18 horse joints which had previously been treated with 1–2 injections of 2 ml PAAG for clinically and radiologically diagnosed OA. Results: Integration of the injected gel was evident at day 10 in the rabbit and by day 14 in the horse, with proliferation and invasion of synovial cells into the gel. By day 90 in rabbit joints and day 30 in horse joints, the gel had formed a sub-synovial layer, which was traversed by thin strands of connective tissue with vessels and covered by a synovial lining facing the joint cavity. This histological appearance persisted up to 2 years post-injection in horse joints. Conclusion: Intra-articular injection of PAAG results in a stable, long-lasting sub-synovial layer of gel traversed with thin strands of connective tissue. Further studies to explore potential effects on synovial inflammation and pain are warranted.